Ganjar Pranowo's Personal Branding on Social Media in the Ganjar Stalls Program - Jihan Juki Okvianti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Social media is widely known by the public only for communicating between individuals, but currently social media is not only used as a means of communication between individuals, but is also used to form personal branding. One of them is the Instagram social media, Lapak Ganjar @lapak_ganjar, which is an account of the Central Java Governor Ganjar Pranowo's program to build personal branding. Apart from building personal branding, the @lapak_ganjar account is also intended to help Central Java UMKM who have been affected by the pandemi covid-19. Through the Stall Ganjar program, Ganjar Pranowo will get a good perception in the eyes of the public because of his caring attitude towards Central Java UMKM. The purpose of this research is to find out how Ganjar Pranowo forms personal branding through Instagram social media.The method used in this research is descriptive qualitative with data collection techniques used are interviews, documentation studies and literature studies. This research is expected to explain how Ganjar Pranowo forms his personal branding for the people of Central Java. In the Lapak Ganjar program, Ganjar Pranowo impresses that he is a leader who cares about UMKM, a people leader, and a millennial leader with his activeness on Instagram social media. The governor of Central Java, Ganjar Pranowo, is very supportive of UMKM in Central Java, so that Ganjar Pranowo has been named the father of UMKM. This research is expected to be an illustration of personal branding carried out by a politician or a leader.